H1N1 influenza: Does chest radiograph have a role in predicting prognosis? - Sripathi, Smiti; Srivastava, Rajendra (International Journal of Medical Research and Review, 2016)
Aims and Objectives: To assess pattern and distribution of chest ray findings in proven case of H1N1 & To evaluate sequential radiographs to assess progression/ resolution of disease. Material and Methods: Patients presenting to a tertiary care hospital in coastal Karnataka, India, from May 2009 to Feb 2011, who tested positive for H1N1 virus with real time PCR test and underwent chest X ray were included in the study. The pattern and distribution of findings and extent of involvement was studied in the initial chest radiograph. Sequential radiographs were studied for progression of disease. Results: The age of patients ranged from 1 to 65 years with 11 (31.5%) patients in pediatric age group, two patients above 60 years and rest were middle age adults (62.8%). Out of 39 patients, four patients had a normal chest radiograph. In the remaining 35 patients, commonest finding was consolidation (77.1%) followed by ground glass opacity (68.6%). Thirty patients had involvement of both lungs at presentation out of which 17 improved, 12 patients expired and one was discharged on request. Conclusion: Patients with bilateral multizonal involvement at presentation deteriorated faster and had an adverse outcome whereas patients with single zone or unilateral involvement had a better outcome. Consolidation and ground glass opacities, especially if bilateral and multizonal predicted adverse outcome. Chest radiograph can play an important role in assessing pattern and distribution of findings and may help in predicting prognosis.